Regime-Dependent Effects on Stock Market Return Dynamics: Evidence from SAARC Countries - Ahmed, Zobia Israr; Mustafa, Khalid (Asian Development Policy Review, 2019)
This study empirically examines the link between stock market returns and exchange rate fluctuations using monthly data ranging from 1993 to 2016 for selected SAARC countries (Bangladesh, India, Pakistan, and Sri Lanka). In the presence of other macroeconomic factors, dynamic links in the financial markets are investigated using Hamilton's Markov switching approach. The multivariate analysis reveals that stock market returns develop in accordance with two different regimes: during a crisis and when there is no crisis. The study discovered evidence of switching suggesting that stock markets have persistent volatility in bullish trends and are influenced more by currency returns during both calm and turbulent periods. However, stock markets with persistent volatility in bearish trends are influenced more by other macroeconomic factors, in both periods. This implies that movements in the stock market are regime-dependent and transition probabilities between regimes can be affected by certain macroeconomic factors.